Teacher Digital Literacy and Its Impact on the Use of Educational Technology in Banyuwangi Schools: Literasi Digital Guru dan Dampaknya terhadap Pemanfaatan Teknologi Pendidikan di Sekolah Banyuwangi - Nur Widyasari; Khusnul Mazidah; Nur Anim Jauhariyah (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study examines teachers' digital literacy and its impact on the use of educational technology in Banyuwangi schools. The study aimed to analyze the influence of teachers' digital literacy on the quality of educational technology use and to identify the role of training and school managerial support. The study employed a qualitative approach with a case study design. Data collection techniques included in-depth interviews, learning observations, and school policy documentation. Data analysis was conducted thematically through the stages of reduction, presentation, and drawing conclusions using source triangulation. The results indicate that teachers' digital literacy, ongoing training, and managerial support play a significant role in increasing the effective, innovative, and equitable use of educational technology in schools